Serum Vitamin D Levels and Severity of Male Androgenetic Alopecia in North Sulawesi: A Cross-Sectional Study - Thigita Aga Pandaleke; Aryani Adji; Shienty Gaspersz; Dwayne Giovano Pandaleke; Paulus Mario Christopher (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: Androgenetic alopecia (AGA) is the most prevalent type of nonscarring hair loss in men, leading to progressive miniaturization of hair follicles and shortened hair growth cycles. Recent evidence indicates the importance of vitamin D and vitamin D receptor-mediated signaling in regulating hair follicle function. Nevertheless, studies investigating this relationship among Indonesian men remain limited. Objective: To investigate the relationship between serum vitamin D levels and the severity of AGA using the Hamilton–Norwood classification in men. Methods: This cross-sectional analytical study included 30 male patients aged 18–70 years who visited a tertiary referral hospital in North Sulawesi and were diagnosed with AGA. AGA severity was classified as mild, moderate, or severe according to the Hamilton–Norwood classification. Serum vitamin D concentrations were assessed, and Spearman’s rank correlation test was used to evaluate the association between vitamin D levels and AGA severity, with p < 0.05 considered statistically significant. Results: The patients’ mean age was 40.27 ± 11.40 years, and the mean duration of AGA was 8.87 ± 6.58 years. The overall mean serum vitamin D level was 26.56 ± 11.36 ng/mL, with the majority (80%) of subjects classified as vitamin D deficient. A progressive decrease in vitamin D levels was observed with increasing AGA severity (mild: 36.34 ± 14.27 ng/mL; moderate: 22.77 ± 4.90 ng/mL; severe: 20.54 ± 5.09 ng/mL). Statistical analysis revealed a significant negative correlation between serum vitamin D levels and AGA severity (r = −0.57; p = 0.001). Conclusions: In this cross-sectional study, lower serum vitamin D concentrations were significantly associated with greater AGA severity (r = −0.57; p = 0.001). These findings suggest a potential role of vitamin D in the pathogenesis of AGA; however, causality cannot be established based solely on this study design.